English language and the language of development : a Malaysian perspective - Hanapiah, Mohd. Faisal (Faculty of Management and Human Resource Development, UTM, 2004)
English language is the main international language. It is also said that English is the language of progress and development. In this age of Internet and globalization, the use of English has increased tremendously. In Malaysia, English has an impact in certain major developmental areas. This paper investigates, analyzes and further explains the interrelationships between English and the process of development in the country. Discussion includes specific parts of interest: the historical background of English in Malaysia, English and the concept of development communication, functions of English in Malaysia, English and Information Communication Technology (ICT), and roles of English in development. The writer also intends to share with readers the reality and challenges in the use of English in non-native English speaking countries like Malaysia and expresses his ideas on possible recommendation to the issues.